Incorporation of biosynthesized silver nanoparticles on active potato starch films - Nazario-Naveda, Renny (2025)
This study presents the effect of the incorporation of biosynthesized silver nano particles on the properties of biodegradable films made from potato starch and its potential to be used as active material. Silver nanoparticles were manufactured by green route from grape residues and were added in the film gelatinization process at concentrations of 3% and 6% v/v and compared with control films (0%). The silver nanoparticles were characterized by UV-Vis spectroscopy and Dynamic Light Scattering. Films morphology was analysed by SEM. Thermic stability was studied by TGA curves, also, mechanical properties and antibacterial activity were studied. The integration of silver nanoparticles in biodegradable films made from potato starch was confirmed. The increase in the percentage of silver nanoparticles produces an improvement in its mechanical properties, also, TGA analysis shows an improvement on thermal stability attributed to the good integration of the nanoparticles in the polymeric matrix. Finally, films with silver nanoparticles exhibited clear antimicrobial activity against all microorganisms tested.